Load sharing behaviour in piled-raft foundations over sand and clay: An experimental investigation - Pandey G.; Mourya V.K.; Patel D.; Kumar R.; Kumar S. (My University, 2025)
Piled-raft foundations have gained increasing popularity in the past few decades, providing a viable alternative to traditional raft and pile foundations. Despite this, designers are reluctant to apply them frequently in practice due to their complex behaviour and the lack of well-defined guidelines specific to piled-raft foundations. Previous studies have demonstrated that piled-rafts are more effective in reducing settlement and can sustain heavier loads from superstructures. Experimental investigations have been conducted in the present study to ascertain the load-sharing behaviour in piled-raft foundations under vertical loading. Since experimental research on piled-rafts, especially over clay, is quite sparse, small-scale lab tests were conducted on piled-rafts over both sand and clay. Experimental comparisons of unpiled rafts and rafts with piles have been established for a better understanding of the individual and collective response of piles and rafts. Moreover, the effects of a few geometric parameters on the load-bearing capacity of the foundation have been observed. The results showed a significant contribution of the raft to load sharing in piled-raft foundations. It was also observed that the individual load-bearing capacities of the raft and the piles, when summed together, differ from that of the piled-raft foundation due to the interactions between the soil and the foundation components. Observations also supported the fact that increasing the length and number of piles enhances the load-bearing capacity of the foundation. The load-sharing ratio and load improvement ratio increase with the number of piles. Eventually, it can be concluded that piled-rafts are better at minimizing settlement and simultaneously carrying heavier loads. © 2024 MIM Research Group. All rights reserved.